Light Emitting Diodes Based on Inorganic Composite Halide Perovskites. (12th December 2018) - Lian, Xiujun; Wang, Xi; Ling, Yichuan; Lochner, Eric; Tan, Lei; Zhou, Yan; Ma, Biwu; Hanson, Kenneth; Gao, Hanwei
Abstract: CsPbBr3 is a promising type of light‐emitting halide perovskite with inorganic composition and desirable thermal stability. The luminescence efficiency of pristine CsPbBr3 thin films, however, appears to be limited. In this work, light emitting diodes based on CsPbBr3 |Cs4 PbBr6 composites are demonstrated. Both quantum efficiency and emission brightness are improved significantly compared with similar devices constructed using pure CsPbBr3 . The high brightness can be attributed to the enhanced radiative recombination from CsPbBr3 crystallites confined in the Cs4 PbBr6 host matrix. The unfavorable charge transport property of Cs4 PbBr6 can be circumvented by optimizing the ratio between the host and the guest components and the total thickness of the composite thin films. The inorganic composition of the emitting layer also leads to improved device stability under the condition of continuous operation. Abstract : Light emitting diodes based on CsPbBr3 |Cs4 PbBr6 composites are demonstrated with improved quantum efficiency, emission brightness, and device stability. The high brightness can be attributed to the enhanced radiative recombination from CsPbBr3 crystallites confined in the Cs4 PbBr6 host matrix. The unfavorable charge transport property of Cs4 PbBr6 can be circumvented by optimizing the ratio and thickness of the CsPbBr3 |Cs4 PbBr6 composite perovskite layer.